Grid Governance in China's Urban Middle-class Neighbourhoods. (5th March 2020) - Tang, Beibei
Abstract: This article examines the so-called "grid governance" scheme, a widely used grassroots governance strategy implemented in urban China in recent years. Drawing on data collected in multiple cities from 2011 to 2016, it analyses in what ways, and to what extent, the state employs the grid governance scheme to resolve neighbourhood conflicts and reinforce governance in Chinese urban middle-class neighbourhoods. The findings highlight complex interactions under the scheme among the residents, the state and market actors in neighbourhood governance, including the resident volunteers, residents' social groups, residents' committees and property management companies. By coopting middle-class resident volunteers, maximizing the existing political influence of the retired urban elites, and establishing Party organizations in middle-class residential communities, the grid governance scheme has become a major vehicle for resident mobilization and conflict resolution, and a key governance mechanism to reinforce the Party's leadership in middle-class neighbourhoods.